The social cooperative as an innovative form of action for solving social problems - Koptiew, Dorota; Puzio-Wacławik, Bogusława (Social Entrepreneurship Review, 2019)
Both social economy and social innovations are issues that nowadays often intertwine, and can become the instruments that are effective in solving social-economic problems. This paper is dedicated to innovative approaches in solving the social problems through social innovations, particularly social cooperatives, which play an important role in social reintegration. The goal of the paper is to deliver a review on the role of social cooperatives in solving local social problems in Poland. The research was conducted through a thorough analysis of the publications and documents that relate to social enterprises and social cooperativity. In the conclusion it is stated, that social cooperative conception is an innovative approach in solving social problems, especially in the local labour market and in counteracting social services deficiencies. Findings suggest that the effectiveness of social cooperatives is limited by the difficult financial situation of the subjects, and numerous internal and the external barriers.